The Impact of EI Mentoring on Emotional Intelligence, Gratitude, and Stress: A Quasi-Experiment (Journal of Organizational Psychology, 2021)
A growing body of research indicates that emotional intelligence (EI) is an important factor for student success. In this study we examined whether students who participated in an EI mentoring program combined with a smartphone application, showed greater increases in EI than students who didn’t participate in the mentoring program. Factors we examined included changes in emotional intelligence, changes in stress levels and relationships between EI, stress, gratitude and growth mindset. Results indicate that participating in the EI mentoring program increased gratitude. Students with higher levels of EI also had lower levels of stress and higher levels of gratitude.
Keywords: organizational psychology; emotional intelligence; mentoring; stress; college students